Pengaruh Keadilan Distributif, Keadilan Prosedural, Dan Keadilan Interaksional Terhadap Kinerja Karyawan (Studi Pada Karyawan PT Lautan Teduh Interniaga Di Bandar Lampung) - Muhammad Evando Yulianto; Agus Zahron Idris (JURNAL RISET MANAJEMEN (JURMA), 2023)
The purpose of this research is to examine and analyze the effect of distributive justice, procedural justice, and interactional justice on employee performance. This research was conducted at PT Lautan Teduh Interniaga in Bandar Lampung. The type of research in this study is quantitative data using tabulation results from questionnaires, and qualitative data using interview methods. The population in this study were employees of PT Lautan Teduh Interniaga in Bandar Lampung. The data collection technique in this study used non-probability sampling with purposive sampling and obtained 100 respondents. Methods of data collection using questionnaires. Analysis of the research data using the PLS approach and SmartPLS as a calculation tool. The results of the study show that distributive justice, procedural justice and interactional justice have a positive effect on employee performance.